2018
DOI: 10.1161/circinterventions.117.005891
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Effect of Drug-Coated Balloons Is Durable to 3 Years in the Femoropopliteal Arteries

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 183 publications
(68 citation statements)
references
References 28 publications
3
64
0
1
Order By: Relevance
“…Rates of 3‐ and 5‐year freedom from TLR of 83.6 and 83.1%, respectively. Similarly, long‐term outcomes after treatment with the In.Pact Admiral drug‐coated balloon have now been presented at 3‐ and 4‐years . DUS patency (PSVR < 2.5) assessed through 3 years was 69.5% .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of 3‐ and 5‐year freedom from TLR of 83.6 and 83.1%, respectively. Similarly, long‐term outcomes after treatment with the In.Pact Admiral drug‐coated balloon have now been presented at 3‐ and 4‐years . DUS patency (PSVR < 2.5) assessed through 3 years was 69.5% .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, long‐term outcomes after treatment with the In.Pact Admiral drug‐coated balloon have now been presented at 3‐ and 4‐years . DUS patency (PSVR < 2.5) assessed through 3 years was 69.5% . Rates of freedom from TLR with the technology were 84.5 and 76.8%, respectively, although treated lesions were of lower complexity (25.8% chronic occlusions, 8.1% with severe calcification).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, DCBs used in the peripheral space use paclitaxel to prevent restenosis following treatment. Randomized and controlled trials have shown that DCBs are safe and effective to treat patients with femoropopliteal artery disease, and show improved outcomes compared to PTA . However, these trials are composed almost entirely of Caucasian patients.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Circulation: Cardiovascular Interventions, the investigators report the 3-year results of the study. 9 Primary patency adjudicated by duplex Doppler ultrasound was superior in the DCB group (69.5%) compared with the PTA group (45.1%). It is notable that there has been a loss of primary patency from 1 (82%) to 2 years (78%) and now to 3 years.…”
Section: See Article By Schneider Et Almentioning
confidence: 84%
“…It is notable that there has been a loss of primary patency from 1 (82%) to 2 years (78%) and now to 3 years. [7][8][9] Over 3 years, primary patency rates after PTA hovered around 50% suggesting that after the first year, PTA patients that remained patent had a similar trajectory when compared with the DCB group. Similarly, 85% of patients in the DCB group remained free from clinically driven target lesion revascularization (TLR) at 3 years compared with 69% in the PTA group.…”
Section: See Article By Schneider Et Almentioning
confidence: 99%